2018
DOI: 10.1088/1361-6439/aa9eb1
|View full text |Cite
|
Sign up to set email alerts
|

A two-step sealing-and-reinforcement SU8 bonding paradigm for the fabrication of shallow microchannels

Abstract: Adhesive bonding is a key technique to create microfluidic devices when two separate substrates are used to form microchannels. Among many adhesives explored in microchannel fabrication, SU8 has been widely used as an adhesive layer for sealing the microchannel sidewalls. The majority of the available SU8-based bonding methods, however, suffer from the difficulties associated with sealing of two important types of the microchannel architecture: (1) shallow microchannels with small patterns on a large area, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…3. The procedure is similar to what we described in our previous work [26] with the difference that the flexible membrane is allowed to deform even after the reinforcement step. Briefly, the patterns of the microchannel sidewalls are created through the glass wet etching procedure.…”
Section: Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…3. The procedure is similar to what we described in our previous work [26] with the difference that the flexible membrane is allowed to deform even after the reinforcement step. Briefly, the patterns of the microchannel sidewalls are created through the glass wet etching procedure.…”
Section: Fabricationmentioning
confidence: 99%
“…In this work, we experimentally and mathematically investigate the volumetric flow rate-pressure difference relationship for the shallow deformable microchannels with ultra-low height-to-width-ratios. The microchannels of few millimeters in width and few microns in height are fabricated by modifying our previously reported fabrication protocol [26] to enable the membrane to freely deform, while the bonding reinforcement allows the high pressure differences to be applied. This fabrication method enables us to uncover new fluid-solid behavioral characteristics for the low-Reynolds-number flow, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcement glass was bonded to the bare side of the membrane using a 16 µm SU8 layer (E ∼ 2 GPa) 23 . The blank glass slides were used for reinforcement of rigid channels to avoid membrane deformations 24 . Capturing adhesive layers in the model.…”
Section: Methodsmentioning
confidence: 99%
“…Cross-linked and hard baked SU8 possesses excellent adhesion and mechanical properties for temperatures up to ∼340 °C, enabling the possibility of being a permanent part of the system/device, with appreciable chemical and thermal stability. , In a thermal study by Lian et al, commercial SU8 is subjected to TGA (thermogravimetric analysis) and showed a weight loss of only 5% up to a temperature of 310 °C . Because of these prospective characteristics of SU8, it is widely utilized as a dielectric insertion layer in organic solar cells to enhance the efficiency, adhesion layer for bioelectrodes, microfluidic devices, , MEMS/NEMS devices, , fuel cells, and so on.…”
Section: Introductionmentioning
confidence: 99%